Analisis Kinerja Keuangan pada KSP Kopdit Adiguna Kota Kupang - Lodovikus Marionis Nifu; Yohana F. Angi; Novi Theresia Kiak (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This research aims to determine the financial performance of KSP Kopdit Adiguna Kupang during the 2018 - 2022 period. This type of research is descriptive research with a quantitative approach using cooperative financial report data. The data analysis technique used is financial ratio analysis. The results of this research show that the financial performance of KSP Kopdit Adiguna is based on profitability ratios in terms of return on assets, return on equity and net profit margin. Return on assets in 2018-2022 is included in the poor criteria, return on equity in 2018-2022 is included in the fairly good criteria and net profit margin in 2018-2022 is included in the good criteria. The liquidity ratio in terms of the current ratio in 2018-2022 is included in the good criteria, while the cash ratio in 2018-2022 is included in the very good criteria. The solvency ratio in terms of total equity to debt ratio and total assets to debt ratio in 2018-2022 is included in the bad criteria.